Analysis Of Students Higher Order Thinking Skills Reviewed From The Speed Of Answering Science Questions - Rifda Nur Hikmahwati Arif; Sitti Saenab; Sulastri; Salma Samputri; M. Arifuddin Jamal; Rifda Mardian Arif (PT ARRUS Intelektual Indonesia, 2024)
This study aims to analyze 1) The Score of Higher-Order Thinking Skills (HOTS) of International Class Program (ICP) students of Science Education Study Program FMIPA UNM, 2) The Score of Higher-Order Thinking Skills (HOTS) of International Class Program (ICP) students in relation to the speed of answering questions. This is a descriptive quantitative research involved 18 students, with an instrument in the form of a Quizizz application-based test. Data were analyzed descriptive statistic based on the distribution of correct answer values and also the time to answer the science questions. The results of the research showed that: (1) The average score of higher order thinking skills of IPA ICP FMIPA UNM students was 42,8 in a medium category. The frequency of students were in the categories Very high was 0% , high was 17%, medium was 33%, low was 44% and Very low was 16%. (2) Students who answered at a moderate speed (21-30 seconds) had the highest average score of 66.67, indicating that moderate time management provides better results than a very fast speed (0-10 seconds) or very slow (≥41 seconds), with scores of 36.67% and 44.17% respectively. This research confirms that moderate management of answering time supports better learning outcomes. To improve HOTS abilities, it is recommended to implement problem-based learning and regular practice of HOTS questions.